A New Circular Intuitionistic Fuzzy MCDM: A Case of Covid-19 Medical Waste Landfill Site Evaluation - Cakir, Esra; Tas, Mehmet Ali; Ulukan, Ziya (2021 IEEE 21st International Symposium on Computational Intelligence and Informatics (CINTI), 2021)
Since the beginning of the COVID-19 pandemic, the use of protective medical products has tremendously increased. The wastes generated by used products pose a threat to public health. Selection of alternative landfill sites to be determined for medical waste is a challenging task as there are several criteria to consider. Fuzzy multi-criteria decision making (MCDM) approaches can be employed to overcome this problem. In this study, the landfill sites evaluation for Covid-19 pandemic medical waste is investigated. Decision-makers give their judgments with intuitionistic fuzzy numbers and a novel circular intuitionistic fuzzy MCDM approach is developed for evaluating sites. As a contribution to the literature, this study extends the usage of circular intuitionistic fuzzy sets (C-IFS) in MCDM approaches by proposing defuzzification functions. The application of the proposed method is intended to guide future C-IFS MCDM methodologies.